Inoculação com fungos micorrízicos arbusculares favorece atributos bioquímicos do solo em diferentes cultivares de cana-de-açúcar (Saccharum officinarum) - Sales, Flávia Reis (2017)
Microbial biomass is defined as a living and active part of the soil, consisting of microorganisms that operate in the decomposition of organic matter, representing a reservoir of nutrients for plants, acting on sustainability and productivity in ecosystems. It is considered an indicator that is sensitive to environmental and anthropogenic changes and it is used as a tool to guide the planning and evaluation of soil management practices. In this context, the aim of this study was to evaluate the effect of inoculation with arbuscular mycorrhizal fungi in different sugarcane (Saccharum officinarum) cultivars, on the biochemical attributes in an Oxisol. The experiment was conducted in the field of LavrasMG, in a sugarcane production area of Bocaina Agroindústria e Comércio de Cachaça Ltda. The soil was classified as a Deep Latosol (LVdf), deep, well drained and very clayey, whose chemical characteristics were: pH = 6.5; Ca = 2.90 cmolc dm -3 ; Mg = 1.3 cmolc dm -3 ; Al = 0 cmolc dm -3 ; Q = 1.1 mg dm -3 ; K = 28 mg dm -3 ; V = 67%; MO = 2.61 g kg -¹. Six sugarcane cultivars were used (CTC1, CTC7, CTC9, CTC16, SP891115 and RB925345); the statistical design was DBC, factorial 6 x 2, with 3 replications involving six cultivars, with and without inoculation of FMAs obtained from trap plants existing in a greenhouse in the Biology, Microbiology and Soil Biological Processes Department in the Soil Science Department of Federal University of Lavras (UFLA), totaling 36 plots during two harvests. Total organic carbon (COT), total soil nitrogen (N-total), microbial biomass carbon (C-BM), microbial biomass nitrogen (N-BM), microbial respiration, enzymatic activities of β-glucosidase, urease, acid phosphatase and fluorescein diacetyl hydrolysis (FDA), were evaluated. The data were submitted to analysis of variance and the means were compared by the Scott Knott test at 5% probability, using the statistical program Sisvar. According to the analysis of variance, it was found that there was a significant effect for the interaction Cultivar x Inoculation with FMAs on N-total, C-BM, qCO 2, enzymatic activities of β-glucosidase, urease and FDA. The mean values for the inoculated treatments were higher, when compared to non-inoculated treatments, evidencing that inoculation with FMAs has a beneficial effect on the native soil microbiota, with a greater emphasis on the biochemical attributes evaluated for CTC7.